Characteristics and composition of atmospheric aerosols in Phimai, central Thailand during BASE-ASIA - Li, Can; Tsay, Si-Chee; Hsu, N. Christina; Kim, Jin Young; Howell, Steven G.; Huebert, Barry J.; Ji, Qiang; Jeong, Myeong-Jae; Wang, Sheng-Hsiang; Hansell, Richard A.; Bell, Shaun W. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Comprehensive measurements of atmospheric aerosols were made in Phimai, central Thailand (15.183 degrees N, 102.565 degrees E, elevation: 206 m) during the BASE-ASIA field experiment from late February to early May in 2006. The observed aerosol loading was sizable for this rural site (mean aerosol scattering: 108 +/- 64 Mm(-1); absorption: 15 +/- 8 Mm(-1); PM10 concentration: 33 +/- 17 mu g m(-3)), and dominated by submicron particles. Major aerosol compounds included carbonaceous (OC: 9.5 +/- 3.6 mu g m(-3); EC: 2.0 +/- 2.3 mu g m(-3)) and secondary species (SO42-: 6.4 +/- 3.7 mu g m(-3), NH4+: 2.2 +/- 1.3 mu g m(-3)). While the site was seldom under the direct influence of large forest fires to its north, agricultural fires were ubiquitous during the experiment, as suggested by the substantial concentration of K+ (0.56 +/- 0.33 mu g m(-3)). Besides biomass burning, aerosols in Phimai during the experiment were also strongly influenced by industrial and vehicular emissions from the Bangkok metropolitan region and long-range transport from southern China. High humidity played an important role in determining the aerosol composition and properties in the region. Sulfate was primarily formed via aqueous phase reactions, and hygroscopic growth could enhance the aerosol light scattering by up to 60%, at the typical morning RH level of 85%. The aerosol single scattering albedo demonstrated distinct diurnal variation, ranging from 0.86 +/- 0.04 in the evening to 0.92 +/- 0.02 in the morning. This experiment marks the first time such comprehensive characterization of aerosols was made for rural central Thailand. Our results indicate that aerosol pollution has developed into a regional problem for northern Indochina, and may become more severe as the region's population and economy continue to grow. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: SOUTHEAST-ASIA; AIR-QUALITY; RADIATIVE PROPERTIES; SIZE DISTRIBUTIONS; TROPOSPHERIC OZONE; ELEMENTAL CARBON; ACE-ASIA; PARTICLES; CHINA; FINE